Analysis of The Effect of Good Corporate Governance Structure on The Integrity of Financial Statements and Their Impact on The Quality of Financial Statements - D. Simamora, J. Melda; Setiyawati, Hari (UNIVERSITAS PAKUAN, 2023)
This research aims to examine the influence of the Good Corporate Governance structure on the integrity of financial statement and its impact on quality of financial reporting. By taking this population research, energy sector companies listed on the Indonesia Stock Exchange in 2016- Year 2020. The research sample was selected using purposive sampling technique and obtained a sample of 31 companies with period 5 years so that 155 samples were obtained . Data analysis techniques were performed using data panel regression and hypothesis testing using eviews 11 and sobel test. Good Corporate Governance is proxied by Institutional ownership, Managerial ownership, Independent Board on Directors, and Audit Commitees. Integrity of financial statement is proxied by Price Book Value. Financial reporting quality is proxied by Timeliness. Based on the results data panel regression analysis with a significance level of 10%, then the results. This study shows that only the managerial ownership variables has an impact on financial reporting quality. For other variables have no effect on the integrity of financial statements and have no impact on financial reporting quality.